2021
DOI: 10.1108/cms-10-2019-0364
|View full text |Cite
|
Sign up to set email alerts
|

How does mentoring influence protégés’ work engagement? Roles of perceived organizational support and family-like employee-organization relationship

Abstract: Purpose Drawing upon organizational support theory and family-like exchange perspective, this paper aims to investigate whether mentoring influences protégés’ work engagement, and the roles of perceived organizational support (POS) and family-like employee-organization relationship (FEOR) between mentoring and protégés’ work engagement. Design/methodology/approach Matched data were collected from 290 protégés and their mentors in two large state-owned enterprises in Northwest China. Multiple regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Thus, perceived organizational support will not affect temporary staff performance without the employeeorganization relationship variable as a mediating variable. The study observations are consistent with prior research (Yang, F., Liu, P., & Xu, 2021;Bal & Tan, 2014;Shih et al, 201;Li et al, 2020).…”
Section: Effect Of Perceived Organizational Support On Temporary Staf...supporting
confidence: 92%
See 2 more Smart Citations
“…Thus, perceived organizational support will not affect temporary staff performance without the employeeorganization relationship variable as a mediating variable. The study observations are consistent with prior research (Yang, F., Liu, P., & Xu, 2021;Bal & Tan, 2014;Shih et al, 201;Li et al, 2020).…”
Section: Effect Of Perceived Organizational Support On Temporary Staf...supporting
confidence: 92%
“…From these numbers, it is logical to argue that that the hypothesis regarding the relationship between perceived organizational support and the employee-organization relationship has a positive and significant effect; the assumption is accepted. The results of this study are in line with the research (Yang, F., Liu, P., & Xu, 2021;Ekowati & Andini, 2008;Lv, 2018).…”
Section: Effect Of Perceived Organizational Support On the Employee-o...supporting
confidence: 91%
See 1 more Smart Citation
“…Finally, previous empirical research has also shown that employees can enhance creative performance from the complex social interaction among the actors in the social network (Perry-Smith and Mannucci, 2015 ; Zhou and Wu, 2018 ), for example, the mentoring relationship that has the attribute of a consistent interaction (Sun et al, 2014 ; Yang F. et al, 2021 ). Thus, the amount of mentoring provided by mentors can enhance the creative performance of mentors.…”
Section: Hypotheses Developmentmentioning
confidence: 95%
“…A mentor’s mentoring support helps the protégé to have a better grasp of the job environment by acquiring skills, which may lead to less uncertainty about the expectations connected with their responsibilities in the company. It enables the mentee to enhance job-related abilities ( Yang et al, 2021 ). Additionally, mentoring is favorably associated with mentees’ learning, which influences mentees’ job performance, according to Chatterjee et al (2021) .…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%